The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1098/rsos.211631
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic rounding: implementation, error analysis and applications

Abstract: Stochastic rounding (SR) randomly maps a real number x to one of the two nearest values in a finite precision number system. The probability of choosing either of these two numbers is 1 minus their relative distance to x . This rounding mode was first proposed for use in computer arithmetic in the 1950s and it is currently experiencing a resurgence of interest. If used to compute the inner product of two vectors of length n in floating-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Stochastic rounding has drawn a lot of attention in various domains [14], [19], [22], [23] due to its efficiency compared to the default rounding mode. The fact that SR-nearness satisfies mean independence (a weaker property than independence) leads to an expected value that coincides with the exact value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stochastic rounding has drawn a lot of attention in various domains [14], [19], [22], [23] due to its efficiency compared to the default rounding mode. The fact that SR-nearness satisfies mean independence (a weaker property than independence) leads to an expected value that coincides with the exact value.…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic arithmetic has two main applications [14]. First, it can be used to estimate empirically the numerical error of complex programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…round(•) denotes the rounding function. Here we adopt the stochastic rounding [15] as it theoretically guarantees smaller probabilistic error bounds [16] compared to the nearest rounding. Specifically, it can be formulated as…”
Section: Head-wise Activation Quantizationmentioning
confidence: 99%
“…Second, SR can be used as a replacement for the default deterministic rounding mode in numerical simulations. It has been demonstrated that in multiple domains such as neural networks, ODEs, PDEs, and Quantum mechanics [8], SR provides better results compared to the IEEE-754 default rounding mode [3]. Connolly et al [23] show that SR successfully prevents the phenomenon of stagnation that takes place in various applications such as neural networks, ODEs and PDEs.…”
Section: Introductionmentioning
confidence: 99%